Isotherms for adsorption of boron onto new fibrous adsorbent containing glycidol ligands: Linear and nonlinear regression methods - Afolabi, H.K. (IOP Publishing Ltd, 2021)
The most appropriate way to design and evaluate an adsorption system performance is by having an idea of the equilibrium relationship, which is also known as adsorption isotherms. The adsorption isotherms provide information on how pollutants such as boron are interacting with adsorbent materials. A novel glycidol-containing adsorbent for selective boron removal was synthesised by radiation-induced grafting of N-vinylformamide (NVF) onto non-woven polyethylene/polypropylene (PE/PP) fiber, followed by hydrolysis and chemical treatment. The adsorbent equilibrium behaviour was investigated using the Langmuir, Freundlich, and Redlich-Peterson isotherms. Comparison of linear and non-linear regression methods was used to determine the most suitable isotherm that best describes the boron adsorption by the new adsorbent. The non-linear method is a better way of obtaining isotherm parameters. The best-fitting isotherm was found to be the Redlich-Peterson (R2 > 0.99) and Langmuir isotherms (R2 = 0.99). Â© Published under licence by IOP Publishing Ltd.